2017
DOI: 10.3233/jad-161099
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Normal Aging from Alzheimer’s Disease: A View from Cognitive Neuroscience

Abstract: Both normal aging and Alzheimer’s disease (AD) are associated with changes in cognition, grey and white matter volume, white matter integrity, neural activation, functional connectivity, and neurotransmission. Obviously, all of these changes are more pronounced in AD and proceed faster providing the basis for an AD diagnosis. Since these differences are quantitative, however, it was hypothesized that AD might simply reflect an accelerated aging process. The present article highlights the different neurocogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
92
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 236 publications
6
92
0
3
Order By: Relevance
“…Disentangling brain changes specific to aging versus AD has been a challenge (Fjell et al, 2014;Jagust, 2013). For example, whether AD neurodegeneration represents accelerated aging or a distinct process has not been fully resolved (Brayne and Calloway, 1988;Buckner, 2004;Ghosh et al, 2011;Toepper, 2017). We sought further insight into this topic by examining grey matter (GM) changes across the lifespan and AD conjointly.…”
Section: Introductionmentioning
confidence: 99%
“…Disentangling brain changes specific to aging versus AD has been a challenge (Fjell et al, 2014;Jagust, 2013). For example, whether AD neurodegeneration represents accelerated aging or a distinct process has not been fully resolved (Brayne and Calloway, 1988;Buckner, 2004;Ghosh et al, 2011;Toepper, 2017). We sought further insight into this topic by examining grey matter (GM) changes across the lifespan and AD conjointly.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies are available such as positron-emission tomography (PET) imaging and monitoring levels of Aβ and tau in cerbrospinal fluid (Masters et al, 2015). Co-morbidities that can exist due to aging such as hippocampal sclerosis further complicate AD diagnosis(Toepper, 2017). Furthermore, questions have been raised regarding whether or not AD is simply an accelerated form of aging due to them both being associated with changes in cognition (Toepper, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Co-morbidities that can exist due to aging such as hippocampal sclerosis further complicate AD diagnosis(Toepper, 2017). Furthermore, questions have been raised regarding whether or not AD is simply an accelerated form of aging due to them both being associated with changes in cognition (Toepper, 2017). However, studies have identified clear neurocognitive differences in cognition, brain size and function in AD compared to healthy aged subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative neurocognitive differences between AD and normal aging clearly suggest that AD cannot be simply regarded as an accelerated aging process 6 . A more heuristic hypothesis, however, would embrace the hypothesis that there may be several distinct upstream pathogenetic pathways that are driven by one or more basic mechanisms of biological aging, all of which lead to a common downstream pathway of beta amyloidosis, tauopathies and inflammation 7 .…”
mentioning
confidence: 99%